Implementasi Spiritualitas Kongregasi Suster-Suster Dina St. Yoseph dalam Pendidikan Karakter Anak di Asrama Wojtyla Tomohon - Marthinus Marcel Lintong; Maritje Maria Makalew (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2025)
This title is based on one of the essential elements of DSY Congregational Spirituality, namely implementing the Spirituality of DSY Sisters in forming the character of children in the dormitory which is the responsibility of the formator. The purpose of this study is to describe the duties and missions in the midst of forming boarding children which are managed directly by the Congregation of DSY Sisters, by implementing the spirituality of the DSY Congregation in building the character of the children in the Wojtyla dormitory. Considering the needs in the field of education in the city of Tomohon which are growing, where children who come are not only from the Manado territory but also from outside the territory of Manado. In the results of research, it was found that children who can be responsible and independent, certainly do not have difficulty adjusting to the existing dormitory environment, especially by following various regulations applied in the dormitory.